Apple Fruit Storage Technology - Nazirova Rakhnamohon Mukhtarovna; Hursanaliyev Shohjaxon; Usmonov Nodirjon Botiraliyevich (Genius Journals, 2022)
This article discusses the effect of preparations based on ethylene on the safety of apple fruits. Ethylene-producing drugs have been found to reduce the activity of the peroxidase enzyme
Keywords: storage; preservation; storage factors; concentration